Gastric-filling ultrasonography to evaluate gastric motor function in patients long-term bedridden undergoing stroke - Xu, Jing; Li, Xiaoxuan; Xue, Kaiwen; Xu, Ying; Ye, Ruixue; Zhao, Jingpu; Fan, Xuehui; Shan, Linlin; Wang, Yulong (Frontiers in Physiology, 2025)
ObjectivesGastric motor dysfunction is a common symptom in patients with stroke, yet lacks objective evaluation methods. This study aimed to assess the feasibility of using gastric filling ultrasonography to evaluate gastric motor function in patients undergoing stroke, and to explore the relationship between gastric ultrasound indicators and clinical features.MethodsWe conducted a case-control study where all participants underwent a 60-minute ultrasound examination after consuming a 300 mL test meal. The cross-sectional area (CSA) of the gastric antrum was measured at four-time points: fasting for six to eight hours (T0), immediately after the test meal (T1), and at 30 (T30) and 60 (T60) minutes. Using CSA, we calculated the gastric emptying rate (GER) at T30 and T60 (GER30, GER60). Additionally, we measured the frequency (ACF) and amplitude (ACA) of antral contractions, as well as the motor index (MI). We compared these ultrasound parameters between the two groups and evaluated their correlation with clinical features such as bed rest time, consciousness level, albumin or hemoglobin levels.ResultsWe recruited 37 stroke patients and 31 healthy controls. Stroke patients exhibited lower GER compared to controls, particularly evident at T30. Additionally, stroke patients showed significantly reduced ACA, ACF, and MI at T1 and T30, with ACA being the only measure showing statistical differences at T60. Correlation analysis revealed negative associations between ACA, GER30, GER60, MIT1 and bed rest time. For predicting anemia, GER30 had a cut-off of 31.52 (88% specificity, 50% sensitivity), while ACAT60’s cut-off was 23.64 (76% specificity, 75% sensitivity).ConclusionUltrasound measurement of gastric filling shows promise as a valuable screening tool for detecting reduced gastric motor function in patients with stroke.